Development of actors and artefacts taxonomy for social research network sites - Ruzainisuhanaliza, Abdul Muni (2018)
The term ‘Social Research Network Sites’ (SRNS) is coined for web-based services that support and enhance research activities. Being introduced to various choices of SRNS, issues arise regarding different inner services and functionalities being provided by these SRNS which depends on their service providers and specific purposes. Consequently, members of researchers’ community need to get themselves registered to more than one SRNS to suit their research necessities. They have to manage few different SRNS to align, share and get information from each of these applications which is inconvenient for researchers. This study proposes a solution for this issue in a model of Actors and Artefacts Taxonomy for Social Research Network Sites. A mixed methods study and analysis to determine significant actors and artefacts for SRNS has been carried out. There are three main objectives of the study which are (i) to identify actors and artefacts discussed in previous works and exists in current applications to support SRNS, (ii) to validate the identified actors and artefacts and discover relationship between them in supporting SRNS and (iii) to develop a taxonomy of actors and artefacts for SRNS. To achieve the first objective, content analyses on scientific documents as well as latest SNS and SRNS applications have been implemented. Questionnaire survey has been constructed and distributed to collect data regarding actors’ perception towards SRNS artefacts. Targeted respondents for this survey are Malaysian researchers’ community who have experiences in using Social Network Sites (SNS) or SRNS for their research purposes. Factor analysis has been performed to categorize artefacts under same components. Finally, a taxonomy is developed. The final result of the study provides significant actors and artefacts to be considered to exist in SRNS. There are five categorization levels which are main category, generic category, subcategory, further subcategory and finally, actual unit of analysis. ‘Actors and Artefacts for Social Research Network Sites’ is labelled as the main category. ‘Actor’ and ‘Artefact’ are generic categories. This is the main structure predefined for the taxonomy according to the first objective. Then, subcategories are derived from the analysis result and listed according to their priority level. There are three suggested actors for SRNS i.e., ‘Research Community’, ‘Organization Administrator’, and ‘System Administrator’. As for the artefacts, there are eight suggestions available i.e., ‘Repository’, ‘Talk’, ‘Report’, ‘Profile’, ‘Fund’, ‘Tool’, ‘Privacy’, and ‘Facility’. Further subcategories are expansion for subcategories. The proposed actors and artefacts taxonomy for SRNS is an initiative to provide feasible suggestion of actors and artefacts to be considered by companies and developers to develop a practical SRNS. By referring this taxonomy, companies and developers may take into consideration upon each actors and artefacts as well as their categorization to be included in their SRNS design to prepare a comprehensive SRNS application environment to serve the researchers community needs.